Ważyk – Ford – Starski. Historia pewnego scenariusza - Małgorzata Hendrykowska, Małgorzata Hendrykowska (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The article presents the complicated story of a script, originally titled “ID Card”, was written in mid-1948 by Adam Ważyk. Had the script been approved for production, it would have been one of the first Polish post-war feature films. However, this did not happen. Apart from Adam Ważyk, Aleksander Ford, Jan Fethke and Ludwik Starski also worked on subsequent versions of the script. Due to complex political circumstances, none of the versions presented was approved by decision-makers. The author presents subsequent versions of the script which change along with social and political changes in Poland. The last version entitled “False Papers”, written by Ludwik Starski in 1968, contains clear elements of an action film. However, this was not a good time for this type of production. Over a period of 20 years, the script of “False Papers” underwent a peculiar metamorphosis: from a political pamphlet, to a didactic story, and finally, an action film with an unexplained mystery and war in the background. None of these versions became a film.